The Relationship Between Mother Knowledge About Complementary Feeding To Toddler’s Nutritional Status In Playground And Kindergarten At Ketindan Village Lawang District Malang Regency - Sugianto, Julius Albert; Andre, Laurentius; Djuari, Lilik (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2022)
Introduction :Nutritional status is the reflection of daily nutrient intake. Determinants affecting nutritional status are adequate dietary intake, sanitation, clean water, infectious diseases, food availability, breastfeeding, supplementary feeding, mother's knowledge and parenting. Incorrect complementary feeding can cause nutritional problems in children. Method : This research is an observational analytic study with cross sectional method. Research sample involved 39 pairs of mother and toddler. Primary data were obtained from complementary feeding questionnaires to mothers and measurement of nutritional status of toddler using weight and height measurement. The research data were processed by statistics at 5% significance level and 95% confidence interval through SPSS 23.0.0 for Windows edition 64 bit, 2015, SPSS Inc. Chicago, IL, USA and Microsoft Office 2016. Result :The results of the research data tested with chi square method, due to the unfulfilled expected value, the Fischer test is used. Research showed mothers knowledge about complementary feeding majority is good (74,4%), majority of toddlers in playground and kindergarten have good nutrition status (82,1%). Fisher exact test gave p>0.05 (p=0,242 (CI = 95%; PR 2.679 (0.482-14.893)) in determining relation between mother knowledge about complementary feeding with nutritional status of toddler at playground and kindergarten in Ketindan Village, Lawang District, Malang Regency. Conclusion : There is no relation between mother's knowledge about complementary feeding to nutritional status of toddler at playground and kindergarten in Ketindan Village, Lawang District, Malang Regency (p=0,242 (CI = 95%; PR 2.679 (0.482-14.893)). Keyword: Nutritional Status, Toddler, Complementary Feeding, Mothers’ Knowledge